The Relationship of Parental Social Support to Student Career Planning - Silvia Junita; Azrul Said; Zadrian Ardi (Universitas Negeri Padang, 2020)
This research is motivated by there are still students who experience difficulties and obstacles in planning their careers. This study aims to describe student career planning, describe parental social support and examine the relationship between parental social support and student career planning. This research is in the form of correlational descriptive with a sample of 269 students. The instrument used was a questionnaire in the form of a Likert scale. From the research results it is known that students' career planning is in the good category, parental social support is in the high category and there is a significant positive relationship between parental social support and student career planning